Inhaled NO at a crossroads in cardiac surgery: current need to improve mechanistic understanding, clinical trial design and scientific evidence - Muenster, Stefan; Zarragoikoetxea, Iratxe; Moscatelli, Andrea; Balcells, Joan; Gaudard, Philippe; Pouard, Philippe; Marczin, Nandor; Janssens, Stefan P. (Frontiers in Cardiovascular Medicine, 2024)
Inhaled nitric oxide (NO) has been used in pediatric and adult perioperative cardiac intensive care for over three decades. NO is a cellular signaling molecule that induces smooth muscle relaxation in the mammalian vasculature. Inhaled NO has the unique ability to exert its vasodilatory effects in the pulmonary vasculature without any hypotensive side-effects in the systemic circulation. In patients undergoing cardiac surgery, NO has been reported in numerous studies to exert beneficial effects on acutely lowering pulmonary artery pressure and reversing right ventricular dysfunction and/or failure. Yet, various investigations failed to demonstrate significant differences in long-term clinical outcomes.The authors, serving as an advisory board of international experts in the field of inhaled NO within pediatric and adult cardiac surgery, will discuss how the existing scientific evidence can be further improved. We will summarize the basic mechanisms underlying the clinical applications of inhaled NO and how this translates into the mandate for inhaled NO in cardiac surgery. We will move on to the popular use of inhaled NO and will talk about the evidence base of the use of this selective pulmonary vasodilator. This review will elucidate what kind of clinical and biological barriers and gaps in knowledge need to be solved and how this has impacted in the development of clinical trials. The authors will elaborate on how the optimization of inhaled NO therapy, the development of biomarkers to identify the target population and the definition of response can improve the design of future large clinical trials. We will explain why it is mandatory to gain an international consensus for the state of the art of NO therapy far beyond this expert advisory board by including the different major players in the field, such as the different medical societies and the pharma industry to improve our understanding of the real-life effects of inhaled NO in large scale observational studies. The design for future innovative randomized controlled trials on inhaled NO therapy in cardiac surgery, adequately powered and based on enhanced biological phenotyping, will be crucial to eventually provide scientific evidence of its clinical efficacy beyond its beneficial hemodynamic properties.